Faktor yang Mempengaruhi Perempuan Berkeinginan Menjadi Ibu - Erna Puspita Sari; Imami Nur Rachmawati (Jurnal Keperawatan Silampari, 2022)
This study aims to identify factors associated with the desire to become a mother. The research method uses a systematic review of three databases, Science Direct, JSTOR, and EBSCOhost, in published articles from 2017 to 2021. The results of the study found 1,417 related articles and 12 articles that met the inclusion criteria related to factors related to a woman's desire to become a mother and have children. Several factors influence a woman to become a mother and have children, including age, employment status, social and economic conditions, social norms, religion, relationship commitment, and health conditions. After marriage, the desire to increase the number of children is also influenced by the desire to have children of a specific gender, which is also associated with local culture. In conclusion, a woman's desire to become a mother and have children is individual, with many factors influencing it. Keywords: Desire to Be a Mother, Woman